Synthesis and application of novel carbohydrate-based ammonium and triazolium salts. Issue 18 (17th September 2019) - Nemcsok, Tamás; Rapi, Zsolt; Bagi, Péter; Bakó, Péter
Abstract: The synthesis of nine new carbohydrate-based quaternary ammonium salts and two new triazolium salts starting from d -glucose has been accomplished. Our synthesis utilized the regio- and stereoselective ring opening reaction of 2, 3-anhydro sugars by nucleophilic reagents to afford the key intermediates. In these new types of phase transfer catalysts, the ammonium and triazolium functions are directly attached to the carbohydrate scaffold in different positions (2-, 3-, 6-positions of the sugar). The efficiency of the altrose- and glucose-based quaternary salts were tested in the alkylation of N -(diphenyl) methylene glycine tert -butyl ester with benzyl bromide. To our knowledge this is the first example when sugar-based quaternary ammonium or triazolium salts were used successfully as phase transfer catalysts. The enantiomeric recognition ability of the synthesized salts towards racemic Mosher's acid silver salt was also investigated by 19 F NMR spectroscopy. Graphical Abstract: